THE IMPACT OF VIOLENT SOCIAL MEDIA CONTENT ON STUDENTS' SOCIAL ANXIETY - LiLi Dianah (Institut Pendidikan Indonesia, 2025)
The increasing use of social media and the ease of access to information have made social anxiety among university students an issue that requires special attention. This study aims to reveal the impact of violent content on social media on the level of social anxiety among students of the Social Studies Education Program at IPI Garut. The research employed a survey method with a correlational quantitative approach, allowing the measurement of the strength of the relationships between the studied variables. Data were collected through an online questionnaire distributed via the Google Forms platform. A total of 108 active students participated as respondents in this study. The respondents were selected using a proportional stratified random sampling technique. The main instrument for data collection was a questionnaire distributed online to the students. The analysis results showed a significant relationship between the consumption of violent content on social media and students' social anxiety. It was found that there was a strong correlation for the indicator of hate speech and toxic text content at 0.635, a strong correlation for exposure to violent images/graphics at 0.760, a strong correlation for algorithmic reinforcement of violent content at 0.699, and a moderate correlation for real-world violent content at 0.593 Keywords: Social media, violent content, social anxiety.